2013
DOI: 10.1097/rhu.0b013e31829d4e82
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perspectives on Pediatric Rheumatology Care and Service Delivery

Abstract: A well-coordinated network of services, timely and accurate information about the illness, treatment and support services, adequate pharmacy support, and school-based advocacy are proposed to be needed to ensure pediatric rheumatology services that are accessible and responsive to the needs of patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 31 publications
3
57
0
1
Order By: Relevance
“…The majority of patients told their classroom teachers and gym teachers about their disease and felt that their teachers understood their disease and that the school was supportive. In contrast, other studies have reported problems communicating with teachers , negative experiences with teachers , and a lack of overall understanding about JIA . The results of our study were promising, as a previous study by Asbjørnslett and Hemmingsson identified that “students’ experiences of participation seemed to be linked to their opportunities to establish some cooperation with the teacher, to have a say, and thus influence their own schooling in order to optimize possibilities for adaptation to their learning environments” (10; p158).…”
Section: Discussionsupporting
confidence: 55%
“…The majority of patients told their classroom teachers and gym teachers about their disease and felt that their teachers understood their disease and that the school was supportive. In contrast, other studies have reported problems communicating with teachers , negative experiences with teachers , and a lack of overall understanding about JIA . The results of our study were promising, as a previous study by Asbjørnslett and Hemmingsson identified that “students’ experiences of participation seemed to be linked to their opportunities to establish some cooperation with the teacher, to have a say, and thus influence their own schooling in order to optimize possibilities for adaptation to their learning environments” (10; p158).…”
Section: Discussionsupporting
confidence: 55%
“…Geographical distance created both practical and personal barriers to accessing service needs, including financial, transport, lack of time, fatigue and feelings of isolation. These issues have been reported elsewhere (Gan, Gargaro, Brandys, Gerber, & Boschen, 2010;Tong et al, 2013), and all affected the mothers' physical and emotional well-being (Hoogsteen & Woodgate, 2013).…”
Section: Discussionmentioning
confidence: 70%
“…In one study of CIPS, participants referred to these high levels of pain as 'pain attacks' or ' are-ups', which could occur several times a day and last for hours (34). Similarly, the term ' are-up' was used in seven JIA studies, though this time referring to periods of acute disease (31,(36)(37)(38)(39)(40)(41). Little differences were observed between the experiences of disease and pain ares, with both reported to negatively impact adolescents' lives, including their level of con dence, identity and independence in daily living and social activities (37).…”
Section: Fluctuating Painmentioning
confidence: 99%
“…Adolescents expressed concerns about how long the pain would last, when it would recur, how it would affect their plans and the long-term prospects of requiring medication (33,38,42,50,51,59). Concerns about the future appeared to be more significant for older compared with younger adolescents (38,(50)(51)(52)59) who may be more aware of the implications on their lives due to greater abstract thought in middle to late adolescence (45). Concerns were also expressed more in those who had experienced pain for a shorter period, suggesting that those with longer pain duration may normalise their experiences and learn to adapt their lives to their pain (51).…”
Section: Future Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation